Analisis Alat Bukti dalam Pembuktian Kasus Pidana Pencurian : Studi Kasus Putusan PN Medan No. 1297/Pid.B/2024 - Rini Armianti Berutu; Oktavia Anjelina Saragih; Rosaria Anastasya Sianipar; Bila May; Parlaungan Gabriel Siahaan; Dewi Pika Lubamban Batu (Universitas 17 Agustus 1945, 2024)
This research will examine the Analysis of Evidence in Proving Criminal Theft Cases (Case Study of Medan District Court Decision No. 1297/Pid.B/2024). The method used by the author is descriptive qualitative research within an empirical juridical method, focusing on legal studies based on actual phenomena that occur in the field. This empirical juridical approach involves data collection through direct observation of legal events or actions, as well as an analysis of the application of law in concrete cases.In the context of research on the Medan District Court Decision No. 1297/Pid.B/2024 related to the theft case, the empirical juridical method allows researchers to explore how the law is practically applied in the judicial process, both in terms of the application of legal regulations and how evidence is interpreted and considered by the court. The research findings indicate that the evidence presented in this criminal theft case has a strong and relevant probative value under the applicable legal regulations. Items seized, such as a pair of shorts, a t-shirt, and a VIVO Y27 S mobile phone box, are directly related to the criminal act committed. This physical evidence, when supported by witness testimony and facts revealed in court, can be considered significant indications in proving the defendant's involvement in the theft.